2020
DOI: 10.2147/jir.s232462
|View full text |Cite
|
Sign up to set email alerts
|

<p>Protective Effects of Curcumin and its Nano-Phytosome on Carrageenan-Induced Inflammation in Mice Model: Behavioral and Biochemical Responses</p>

Abstract: Background and purpose: Natural compounds are used for prevention of inflammation. Curcumin has antioxidant and anti-inflammatory properties, and loading it into nano-phytosomes may improve its efficiency. The present study investigates the effects of curcumin and its nanophytosome on behavioral and biochemical responses in carrageenan-induced inflammation in the mice model. Methods: The mice were divided into six groups and received oral administration of curcumin or its nano-phytosome at a dose of 15 mg/kg f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Nanophytosomes protect Oxidative Medicine and Cellular Longevity curcumin and enhance its absorption. Curcumin nanophytosomes probably enhance the action of antioxidant enzymes and/or reduce oxidative stress [40]. In another study, Tan et al examined the antioxidant activity of carotenoids encapsulated in liposome delivery vehicles, and their results showed that encapsulation could improve radical inhibitory activity of carotenoids [41].…”
Section: Discussionmentioning
confidence: 99%
“…Nanophytosomes protect Oxidative Medicine and Cellular Longevity curcumin and enhance its absorption. Curcumin nanophytosomes probably enhance the action of antioxidant enzymes and/or reduce oxidative stress [40]. In another study, Tan et al examined the antioxidant activity of carotenoids encapsulated in liposome delivery vehicles, and their results showed that encapsulation could improve radical inhibitory activity of carotenoids [41].…”
Section: Discussionmentioning
confidence: 99%
“…The nano-phytosome treatment was more antioxidant than curcumin (P < 0.05) in the case of SOD, CAT, GPx, and GR and had a higher latency time compared to curcumin in hot plate and tail-pinch tests. 247 Three studies evaluated the topical effects of three different phytosomes in carrageenan-induced edema in Wistar rats. The Lawsone-containing phytosome complex (Lawsonia inermis L.) had a higher anti-inflammatory effect than plant extract gel at 4 h (P < 0.001).…”
Section: Dovepressmentioning
confidence: 99%
“…The nano-phytosome treatment was more antioxidant than curcumin (P < 0.05) in the case of SOD, CAT, GPx, and GR and had a higher latency time compared to curcumin in hot plate and tail-pinch tests. 247 …”
Section: Biological Activities Of Phytosomesmentioning
confidence: 99%
“… 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 Phytochemicals such as Berberine, and Curcumin present in DKV-O have individually shown efficacy to reduce carrageenan and TPA stimulated inflammation in animal models through the modulation of the cytokines, nitric oxides, cyclooxygenase and prostaglandins. 40 , 63 , 64 , 65 , 66 Furthermore, both Berberine and Curcumin have been observed to modulated the IL-17 and IL-23 expression in the immune cells. 67 , 68 , 69 …”
Section: Discussionmentioning
confidence: 96%